Non-invasive physical plasma for preventing radiation dermatitis in breast cancer: results from an intrapatient-randomised double-blind placebo-controlled trial: original research article - Dejonckheere, Cas S.; Layer, Julian Philipp; Nour, Younèss; Layer, Katharina; Glasmacher, Andrea; Wiegreffe, Shari; Fuhrmann, Arne; Caglayan, Lara; Grau, Franziska; Sarria, Gustavo Renato; Scafa, Davide; Koch, David; et al. (Clinical and translational radiation oncology, 2024)
Background and Purpose - To investigate the effect of topical non-invasive physical plasma (NIPP), a volatile mix generated out of ambient air, on prevention of acute radiation dermatitis (RD) during and after whole-breast irradiation (WBI). - Materials and Methods - Lateral and medial breast halves were randomised within each patient to receive either 120 s of NIPP or sham treatment daily during WBI. Standard skin care with urea lotion was applied to the whole breast. Blinded acute skin toxicity was assessed weekly for each breast half separately and included clinician- (CTCAE) and patient-reported (modified RISRAS), and objective (spectrophotometry) assessments. As an additional external control, a comparable standard of care (SoC) patient collective from a previous prospective trial was used. - Results - Sixty-four patients were included. There were no significant differences between breast halves. Post-hoc comparison with a similar SoC control collective revealed OR = 0.28 (95% CI 0.11-0.76; p = 0.014) for grade ≥ 2 RD upon WBI completion, along with less hyperpigmentation (p < 0.001), oedema (p = 0.020), dry (p < 0.001) and moist desquamation (p = 0.017), pain, itching, and burning (p < 0.001 for each). Tolerability of NIPP was excellent and side effects were not observed. - Conclusion - Even though there were no differences between intrapatient-randomised breast halves, the overall incidence and severity of acute radiation-induced skin toxicity were considerably lower when compared to a prospectively collected SoC cohort. Our data suggest the potential benefit of NIPP in RD prevention. A randomised trial with a physical control group is warranted to confirm these promising results (DRKS00026225).
Online verfügbar: 4. November 2023, Artikelversion: 4. November 2023
Gesehen am 18.07.2024